Sitagliptin ameliorates hypoxia-induced damages in endometrial stromal cells: an implication in endometriosis. Issue 1 (1st January 2022) - Li, Ying; Lv, Xiaolin; Jiang, Mei; Jin, Zhili
ABSTRACT: Hypoxia-induced damage in endometrial stromal cells (ESCs) is an important event in the pathological progression of Endometriosis. It is reported that significant inflammation is induced by hypoxia in ESCs, mediated by serval inflammatory progressions, pathways, or factors. Sitagliptin, an important member of the dipeptidyl peptidase-4 (DPP-4) inhibitors family and has been widely used for the management of type 2 diabetes. It has been recently reported to exert significant anti-inflammatory effects. Here, we aim to assess whether Sitagliptin possesses a protective effect against hypoxia-induced damages in ESCs. Our findings indicate that exposure to hypoxia significantly increased oxidative stress in ESCs by increasing the production of reactive oxygen species (ROS) and decreasing the levels of reduced glutathione (GSH), which was ameliorated by Sitagliptin. Additionally, the excessively produced inflammatory mediators, including tumor necrosis factor (TNF)-α, interleukin (IL)-6, monocyte chemoattractant protein-1 (MCP-1), cyclooxygenase-2 (COX-2), prostaglandin E2 (PGE2 ), and high mobility group box (HMGB)-1, in hypoxia-treated HESCs were pronouncedly repressed by Sitagliptin. The activated p38 mitogen-activated protein kinases (MAPK) pathway was observed in hypoxia-stimulated HESCs, then greatly inhibited by the introduction of Sitagliptin. Lastly, hypoxia-induced phosphorylation and degradation of IκBα, as well as the upregulation of nuclear factor kappa-B (NF-κB) p65 and increased transcriptional activity of NF-κB, were dramatically abolished by Sitagliptin. Collectively, Sitagliptin ameliorated hypoxia-induced damages in ESCs by suppressing the inflammation.